Case Study on the Fingerprint Processing in a Workplace under GDPR Article 9 (2, b) - Bulgakova, Daria (Teisė, 2022)
The protection of personal data is the most important legal standard for the use of biometric data. Fingerprints are personal biometric data in accordance with Article 9 (1) of the GDPR. It is also a category of personal data that needs to be processed specifically in order to ensure the right to the protection of personal data and to reduce the risk of its restriction. The problem discussed in this study is fingerprint processing in the workplace.